Viscosity measurements of the ionic liquid Trihexyl(tetradecyl)phosphonium Dicyanamide [P6,6,6,14][dca] using the vibrating wire technique - Diogo, João C. F. (2015)
The paper reports measurements of the viscosity of the ionic liquid trihexyl(tetradecyl)phosphonium dicyanamide ([P6,6,6,14][dca]) by means of a vibrating wire viscometer; the measurements have been carried out to demonstrate the applicability of the method to studies on electrically conducting liquids. To the knowledge of the authors, the present work reports only the second measurements of the viscosity of ionic liquids, using the vibrating wire method, ever published in the literature. The measurements were carried out at near ambient temperature at atmospheric pressure so that they can be compared with measurements made on the same sample using measurement techniques of previously proven validity. For this purpose measurements have also been carried out with two Ubbelohde capillary viscometers. Density measurements were undertaken using a U-tube Anton Paar density meter. All of the viscosity results reported here are mutually consistent within the estimated uncertainty of ± 2 % of the vibrating wire measurements, which confirms the applicability of the vibrating wire technique. However, the other viscosity literature data for of the same liquid deviate from the present results by more than the mutual estimated uncertainties of the measurements which may arise mainly from the different purities of the two samples.